Islamic Ethics in Business and Finance: Implication for Corporate Governance and Responsibility - Liestyowati, Liestyowati (Accounting Studies and Tax Journal (COUNT), 2024)
This systematic literature review explores the implications of implementing Islamic ethical principles in Good Corporate Governance (GCG) within the context of Islamic financial institutions. The study investigates the relevance and impact of Islamic ethics on various aspects of corporate governance, including accountability, transparency, justice, and stakeholder welfare. Drawing upon a comprehensive review of existing literature, the research identifies key themes and findings related to the integration of Islamic ethical values into GCG practices. The study highlights the significance of aligning corporate governance structures with Sharia principles to ensure ethical conduct, transparency, and stakeholder trust. However, the research also acknowledges several limitations, such as data availability constraints, geographic focus, cultural and social contexts, and methodological considerations. To address these limitations, future research directions are suggested, emphasizing the need for broader data sources, cross-cultural analyses, and diverse research methodologies to deepen understanding and enhance the applicability of findings in diverse organizational settings.